The high burden of comorbidities in Aboriginal and Torres Strait Islander Australians living with chronic hepatitis B in Far North Queensland, Australia, and the implications for patient management. - Jordan Riddell; Allison Hempenstall; Yoko Nakata; Sandra Gregson; Richard Hayes; Simon Smith; Marlow Coates; Lizzie Charlie; Christine Perrett; Victoria Newie; Tomi Newie; Sharna Radlof; et al. (PLoS ONE, 2023)
Background Aboriginal and Torres Strait Islander Australians living with chronic hepatitis B virus (HBV) infection have a significant burden of hepatocellular carcinoma (HCC). The prevalence of comorbidities that increase the risk of HCC in this population is incompletely defined. Methods This cross-sectional study was performed in remote tropical Queensland, Australia in January 2021. All individuals living with chronic HBV in the region were identified; the prevalence of relevant comorbidities was determined by reviewing medical records. Results All 236 individuals in the cohort identified as Aboriginal and Torres Strait Islander Australians; their median (interquartile range (IQR)) age was 48 (40-62) years; 120/236 (50.9%) were female. Of the 194/236 (82.2%) engaged in HBV care, 61 (31.4%) met criteria for HBV therapy and 38 (62.2%) were receiving it. However, 142/236 (60.2%) were obese, 73/236 (30.9%) were current smokers and 57/236 (24.2%) were drinking alcohol hazardously; 70/236 (29.7%) had ≥2 of these additional risk factors for HCC, only 43/236 (18.2%) had none. Among the 19 patients with confirmed cirrhosis, 9 (47%) were obese, 8 (42%) were currently-or had a history of-drinking alcohol hazardously and 5 (26.3%) were current smokers. Patients also had a median (IQR) of 3 (2-4) cardiovascular risk factors (cigarette smoking, hypertension, impaired glucose tolerance, dyslipidaemia, renal impairment/proteinuria). Only 9/236 (3.8%) did not have one of these 5 comorbidities. Conclusions Aboriginal and Torres Strait Islander Australians living with chronic HBV in this region of remote Australia have a high engagement with HBV care and the majority of individuals eligible for antiviral therapy are receiving it. However, a significant comorbidity burden increases their risk of cirrhosis, HCC, and premature death. It is essential to integrate chronic HBV care with management of these comorbidities-rather than focusing on HBV alone-to achieve optimal health outcomes.